Miniature parallel ECT: a preliminary study using COMSOL - Abd Rashid, Wan Norhisyam; Mohamad, Elmy Johana; Abdul Rahim, Ruzairi; Mahmad Ameran, Hanis Liyana; Abdullah, Jaafar; Mohamad, Mimi Mohaffyza; Hashim, Hairulazwan; Shaib, Mohd Fadzli; Marwah, Omar Mohd. Faizan (Penerbit UTM Press, 2015)
The usage of Electrical Capacitance Tomography (ECT) is not limited to the imaging of mixtures in process equipment, it also can be used to measure the concentration profiles of component, and in certain case ECT is being used to investigate the boundaries and phase sizes within vessels and pipelines. There are quite a number of type of ECT sensors such as circular structure, square structure, concentric -annulus and parallel structure which are used for particular applications. In this paper, a study was carried out in order to investigate the behavior of electric field on the miniature parallel ECT. Simulations using COMSOL Multiphysics are being done to study the effect of increasing the size of the test object and the effect of increasing the permittivity of the test object. The results show that (1) the electric field lines relatively follow the phantom shape corresponding to the increasing of the size of the phantom and (2) the electrical field lines seems to bend more around the when the permittivity increases. Presented simulations establish first step of investigation, however already proved its usefulness for ECT performance model validation.